2013
DOI: 10.1371/journal.pone.0054276
|View full text |Cite
|
Sign up to set email alerts
|

SPIN90 Phosphorylation Modulates Spine Structure and Synaptic Function

Abstract: The correct rearrangement of postsynaptic components in dendritic spines is important for driving changes of spine structure and synaptic function. SPIN90 plays an essential role in many cellular processes including actin polymerization, endocytosis, growth cone formation and dendritic spine morphogenesis. Here, we demonstrate that SPIN90, which is a binding partner of PSD95 and Shank in spines, is targeted to synapses and leads to enhanced synaptic activity in neurons. We show, using in vitro and in vivo kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…NCKIPSD has been evidenced to be involved in the building and maintenance of dendritic spines and modulation of synaptic activity in neurones (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NCKIPSD has been evidenced to be involved in the building and maintenance of dendritic spines and modulation of synaptic activity in neurones (33).…”
Section: Discussionmentioning
confidence: 99%
“…showed evidence as an eQTL for AMT, FAM212A, GPX1, NCKIPSD and RNF123 across multiple brain tissues (Supplementary File 1: Tables S5-7). As an example, NCKIPSD encodes a protein involved in the building and maintenance of dendritic spines and modulates neuronal synaptic activity (33 Figure 3). DCC encodes a receptor involved in guiding neuronal growth and is highly expressed in the brain (34).…”
Section: Figure 2 Forest Plot Showing Gwas Associations Of Rs12658032mentioning
confidence: 99%
“…SPIN90/WISH [SH3 protein interacting with Nck, 90 kDa/ Wiskott-Aldrich syndrome protein (WASP) interacting SH3 protein] is another scaffold regulator of actin polymerization in dendritic spines. Overexpression of SPIN90 in cultured neurons increases the number and length of dendritic filopodia/ spines via an N-WASP-independent mechanism, while knockdown of its expression and in knockout mice dendritic spine density and maturation is reduced (81,236,275). SPIN90 binds to PSD-95 and Shank and might work as their downstream effector on spine morphogenesis (81,236,275).…”
Section: A Actin Binding and Cytoskeletal Proteinsmentioning
confidence: 99%
“…Interestingly, the maintenance of LTD is blocked by inhibiting actin depolymerization, as evidenced by the finding that long-lasting forms of LTD are associated with a decrease in filamentous F-actin content in spines (Star et al, 2002 ). Previous studies using neuron cultures have suggested that SPIN90, an ABP is also involved in LTD (Cho et al, 2013a , b ). In this study, we investigated the role of SPIN90 in synapse and behavior by using Spin90 -KO mice.…”
Section: Discussionmentioning
confidence: 98%